STUDY OF DERANGEMENT OF ENZYMES OF LIVER IN MALARIAL P.VIVAX AND P. FALCIPARUM SPECIES - Noman , Obaid (Journal of Biomedical and Pharmaceutical Research, 2018)
The parasite protozoan Plasmodium is what causes malaria, a parasitic illness spread by mosquitoes. In under developed nations, malaria is a serious health issue that causes 2–3 million fatalities annually. Studies have shown that blood infected with malaria exhibits haematologic and biochemical changes, and this illness is frequently accompanied by sequelae. Anemia, thrombocytopenia, and disseminated intravascular are among the haematologic changes linked to malaria infection. When sporozoites enter hepatocytes during the liver stage, this might result in organ congest, sinusoidal obstruction, and cellular inflammation. These hepatocyte alterations may cause parenchyma and membrane damage leading enzymes to leak into the bloodstream. Considerable alterations in biochemical and haematological markers are the fundamental drivers of malaria pathogenesis. As test markers of liver function, haematological values and levels of enzymes aspartate transaminase (AST), alkaline phosphatase (ALP), alanine transaminase (ALT), and bilirubin (total and direct) were examined. The evaluation of these liver enzymes helps to assess the involvement of liver in plasmodium infection and also assess the severity and frequency of involvement along various strains of malaria. Materials and Methods: This prospective study was conducted at the Department of Pathology and Central Clinical Laboratory, JNMC-AVBRH, Sawangi Meghe, Wardha, and DMMC-SMHRC, Nagpur over a period of 2 years. A sample size of at least 180 people was chosen. Among the 180 confirmed malaria cases 82 were of plasmodium falciparum and 98 were of Plasmodium Vivax. the Orth-diagnostics dry chemistry and Beckman Coulter-Au480 to perform tests of liver functions. Conclusion: The analysis of the results obtained in current study led us to conclude that both malarial the Plasmodium vivax and falciparum result in derangement of liver enzymes in majority of the cases. We also found that the derangement in liver enzymes is more pronounced in frequency of occurrence as well as levels of enzyme derangements in infections with Plasmodium falciparum. Total Bilirubin was the enzyme raised most frequently raised enzyme in both the species while alkaline Phosphatase was the least frequently raised enzyme. Keywords: Malaria, Liver Enzymes, Plasmodium, Falciparum, Vivax, Liver function tests, Bilirubin, SGOT, SGPT ALP.